Remarks upon the proposed destruction of the tower of the Parish Church of St. John, Hampstead - Scott, George Gilbert, Sir, 1811-1878 (Salt Lake City, UT : Project Gutenberg, 2020)
"Remarks upon the proposed destruction of the tower of the Parish Church of St. John, Hampstead" by George Gilbert Scott is a letter written during the late 19th century. This book serves as a significant architectural critique and advocacy piece focusing on the proposed demolition of the church's tower, which the author believes to be sound and historically valuable. Scott, an eminent architect of his time, offers insights into the architectural and aesthetic considerations surrounding the church's restoration plans. In this letter addressed to the Vicar of Hampstead, Scott articulately argues against the necessity of demolishing the existing tower, asserting that it remains in excellent condition despite previous claims of structural issues. He details the false premises regarding the tower's subsidence, demonstrating its historical significance and architectural merit. Scott advocates for a more judicious approach to restoring the church, suggesting alternative solutions that preserve the tower while making necessary improvements to the church's interior layout. Ultimately, he underscores the need for appreciation of the existing structure as an essential part of the local heritage, advocating for reforms that respect both the community's history and financial considerations. (This is an automatically generated summary.)
Release date is 2020-05-25
Transcribed from the 1874 J. Hewetson edition by David Price
Keywords: Church architecture -- England -- London; St. John's Parish Church (Hampstead, London, England)